BILATERAL CONGENITAL MYDRIASIS WITH ACCOMPANYING MIXED DEVELOPMENTAL DELAY - Wulandari, Fadhilah Putri; Akib, Marliyanti N.; Maharani, Ratih Natasha; Patong, Rani Yunita (Majalah Oftalmologi Indonesia, 2023)
Introduction: Congenital bilateral mydriasis is a rare condition characterized by fixed dilated pupils unresponsive to light. It may occur associated with cardiovascular syndrome, gastrointestinal malformation, or developmental delay. Referred causes in comprehensive differential diagnosis for congenital mydriasis include alterations in ocular structures, ocular innervation alterations and others secondary to trauma, infection, or topical medication. Case Illustration: A 10 months-old boy presented to the hospital with large pupils in both eyes since birth. He has a persistent pupillary membrane with 9 mm diameter of pupil and unable to respond to light in both eyes. The pupillary response test using pilocarpine solution 0.1% showed no difference in diameter of pupils. Comprehensive pediatric examination revealed developmental delay. Computed tomography and laboratory result (laboratory blood count, toxoplasmosis, and cytomegalovirus) within normal limit. After eight months follow up, no significant change in pupil size or light responsiveness was found. Discussion: Comprehensive examination of anterior to posterior segments of the eyes is imperative on the lookout for underdiagnosed diseases. Clinical assessment remains vital for guiding investigations. Observation is required to detect the presence of certain systemic abnormalities that frequently do not manifest at birth. Conclusion: Congenital mydriasis can be diagnosed quickly in ordinary conditions, but it can be quite challenging when it presents as a coincidental finding of other spectrum diseases. It is important to perform a comprehensive general and eye examination to rule out any serious condition related to it. Keyword: Bilateral congenital mydriasis, dilated pupil, mixed developmental delay, pediatric ophthalmology